THE TASTY OF BRAND PRODUCTS FOR MICRO, SMALL AND MEDIUM ENTERPRISES “BRANCH PURNAMA” - Emmywati, Emmywati; Masyhuri, Mohammad Ali; Setyawan, Mochamad Ardi; Suprihandari, Miya Dewi (International Research of Multidisciplinary Analysis, 2023)
The word “Branch Purnama” is a word that is often read, heard and is a favorite of consumers and lovers of local roadside food in Indonesia, especially in East Java. The word has automatically become a "stamp" to convince new consumers and loyal consumers that they have culinary products and tastes that are the same and "in line" with many other micro, small and medium enterprises everywhere. Although in reality, the facts are not as expected, that is, all of their culinary products refer to a slightly different center, will not the same, for those who know (Aaker, D.A., 2004). However, all of this has aroused the curiosity of many people outside their scope, especially consumers, how come hundreds of micro, small and medium enterprises have made or pinned the same name on the front banner of their culinary establishment, namely the Purnama Branch. What is even more interesting is that these micro, small and medium enterprises mix and set the seasoning for their respective products, not based on ready-to-eat product shipments from the central "Purnama Branch" which most likely does not recognize the "branches" that have existed so far in Indonesia. many places in East Java, especially in Surabaya and its surroundings